2006
DOI: 10.1002/jcp.20607
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activation of latent TGF‐β precedes caspase‐3 activation and enhances apoptotic death of lung epithelial cells

Abstract: Transforming growth factors beta (TGF-betas) are multifunctional cytokines, which are secreted in latent forms in large latent TGF-beta complexes (LL-TGF-beta) with subsequent deposition to the extracellular matrix (ECM). While a variety of mechanisms capable of activating latent TGF-beta in vitro have been described, the physiological conditions, which promote the activation of TGF-beta in vivo are poorly understood. Mink lung epithelial cells (Mv1Lu) are a widely used model for evaluation of the effects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…Others have shown that Akt signaling is a critical mediator of airspace homeostasis in the setting of neonatal and adult hyperoxic injury (63,64). Furthermore, several in vitro studies demonstrate that TGF-β directly inhibits Akt-mediated lung epithelial cell survival (65,66). We show that a similar mechanism may be operative with chronic CS-induced lung injury.…”
Section: Figuresupporting
confidence: 53%
“…Others have shown that Akt signaling is a critical mediator of airspace homeostasis in the setting of neonatal and adult hyperoxic injury (63,64). Furthermore, several in vitro studies demonstrate that TGF-β directly inhibits Akt-mediated lung epithelial cell survival (65,66). We show that a similar mechanism may be operative with chronic CS-induced lung injury.…”
Section: Figuresupporting
confidence: 53%
“…In the present study, TGFb gene was down-regulated in fish fed cMOS, what could be related, among other factors, to a fish system cell proliferation regulation against increased transcripts of Caspase 3 by potentiating PI-3K/Akt and p38 MAPK-dependent survival pathways [59,60]. In other vertebrate species, dietary cMOS supplementation altered not only some anti-inflammatory cytokines expression patterns but also some other related to proinflammatory pathways.…”
Section: Discussionmentioning
confidence: 61%
“…We investigated five apoptosis-associated proteins in NSCLC tissues, namely bcl-2, caspase-3, fas, fasL, and survivin. According to data updates, these proteins may be important for the balance of cell proliferation and cell death to maintain cellular homeostasis in normal lung tissues [24][25][26][27][28]. But their actual roles in can-236 236 236 236 236 In the current study, we found bcl-2, which was originally cloned from the t(14;18) translocation breakpoint found in follicular B-cell lymphomas, to be related to large tumor size in NSCLC.…”
mentioning
confidence: 76%